Circular RNA hsa_circ_0000567 can be used as a promising diagnostic biomarker for human colorectal cancer. Issue 5 (15th January 2018) - Wang, Jianjun; Li, Xiaomin; Lu, Linming; He, Lei; Hu, Haoran; Xu, Zengxiang
Abstract : Background: Recent studies have revealed that circular RNAs are involved in the biological process of some kinds of human cancers. However, little is known about their diagnostic values and functions in colorectal cancer (CRC). Methods: The expression levels of hsa_circ_0000567 in 102 paired CRC tissues and adjacent noncancerous tissues, 5 CRC cell lines, and a normal colorectal epithelial cell line were detected by quantitative real‐time polymerase chain reaction (qRT‐PCR). The correlations between hsa_circ_0000567 expression levels and the clinicopathological factors of patients with CRC were analyzed. Furthermore, the loss‐of‐function assay was performed to investigate the functions of hsa_circ_0000567 in vitro. Finally, a receiver operating characteristic (ROC) curve was established to evaluate the diagnostic value of hsa_circ_0000567. Results: Hsa_circ_0000567 expression was significantly downregulated in CRC tissues and CRC cell lines. In addition, the decreased hsa_circ_0000567 expression in CRC was negatively correlated with tumor size ( P  =   .011), lymph metastasis ( P  =   .003), distal metastasis ( P  <   .0001), and tumor–node–metastasis (TNM) stage ( P  =   .003) in CRC. Moreover, knockdown of hsa_circ_0000567 promoted CRC cells proliferation and migration in vitro. Importantly, the area under the ROC curve (AUC) was 0.8653, which indicates hsa_circ_0000567 can serve as a diagnostic biomarker. Conclusion: Hsa_circ_0000567 may be a novel suppressor and a potential diagnosis biomarker in CRC.